Correlation between Hepatitis B Viral Load and Liver Function Test among Hepatitis B Virus Patients in Khartoum State, Sudan - Sawsan A. A. Altom; Abdelsalam MA Nail; Ahmed Mudawi Musa; Gad Allah Modawe (Sirte Journal of Medical Sciences, 2023)
Hepatitis B virus (HBV) infection is a global public health problem. Sudan is classified among the countries with high hepatitis B virus seroprevalence . The purpose of this study was to study the correlation between the hepatitis B viral load and the liver function test in hepatitis BV patients Descriptive cross-sectional hospital based study conducted at the hepatology clinic Ibn Sinaa teaching hospital, covering all the patients who presented to the clinic from March-April 2018, primary data was collected from the patients and/or their care giver, a specifically designed questionnaire was used, and then the data was re-entered into a predesigned data collection form. A P value of 0.05 or less was considered statistically significant. The Data was analyzed using Social Package Statistical Analysis version (24). A total of 83 patients, 19 (22.9%) have viral load level less than 20 IU, 33(39.8%) have viral ranging between (20-2000IU ML ), 13 (15.6%)have viral load between (2000-20,000IU) and 18(21.7%)have viral load more than 20,000IU) . The study showed a significant correlation between hepatitis B viral load and alanine aminotransferase level (ALT) with a P value of 0.027. The study showed a significant correlation between hepatitis B viral load and aspartate aminotransferase level (AST) with a P value of 0.009 .The study also showed there was a significant relation between hepatitis B viral load and serum albumin level with a P value of 0.007. Hepatitis B viral load was not affected by the age, gender or the duration of the disease. The liver function tests is recommended to be used as an indicator for the hepatitis B viral load and the degree of liver inflammation.